Low Apgar scores at 5 minutes in a low risk population: Maternal and obstetrical factors and postnatal outcome - Salustiano, Eugenia Maria Assunção; Campos, Juliana Alvares Duarte Bonini [UNESP]; Ibidi, Silvia Maria; Ruano, Rodrigo; Zugaib, Marcelo (Elsevier, 2012)
Objective: To evaluate the association between Apgar scores of less than seven at five minutes (AS5min < 7) and antenatal factors and postnatal outcomes. Methods: A retrospective cohort and case-control study of 27,252 consecutive term newborns in a low risk obstetrical population between January 2003 and December 2010. Maternal and infant databases were reviewed from all cases with AS5min < 7 (n = 121; 0.4%) and 363 cases with AS5min ≥ 7 at 5 minutes who were randomly selected by a computer program. The main outcomes were neonatal death, newborn respiratory distress, need for orotracheal intubation and neonatal intensive care unit (NICU), and hypoxic-ischemic-encephalopathy. Results: After multiple regression analysis, repeated late decelerations on cardiotocography (OR: 2.4; 95% CI: 1.4-4.1) and prolonged second stage of labor (OR: 3.3; 95% CI: 1.3-8.3) were associated with AS5min < 7, as well as neonatal respiratory distress (OR: 3.0; 95% CI: 1.3-6.9), orotracheal intubation (OR: 2.5; 95% CI: 1.2-4.8), need for NICU (OR: 9.5; 95% CI: 6.7-16.8), and hypoxic-ischemicencephalopathy (OR: 14.1; 95% CI: 3.6-54.7). No other antenatal factors were associated with AS5min < 7 (p > 0.05). Conclusion: Repeated late decelerations and prolonged second stage of labor in the low-risk population are predictors of AS5min < 7, a situation associated with increased risk of neonatal respiratory distress, need for mechanical ventilatory support and NICU, and hypoxic-ischemic-encephalopathy. © 2012 Elsevier Editora Ltda. All rights reserved.
Baixos índices de Apgar no quinto minuto de vida em população de baixo risco: Fatores maternos e obstétricos e resultados pós-natais
Keywords: Apgar scores; Asphyxia; Delivery; Hypoxic-ischemic-encephalopathy; Neonatal mortality; Term